Sensitive and specific detection of Trypanosoma vivax using the polymerase chain reaction - Masake, R.A.; Majiwa, Phelix A.O.; Moloo, S.K.; Makau, J.M.; Njuguna, J.; Maina, M.; Kabata, J.M.; Ole-MoiYoi, O.K.; Nantulya, V.M. (Elsevier, 1997)
The nucleic acid probes that are currently in use detect and distinguish Trypanosoma vivax parasites according to their geographic origin. To eliminate the need for using multiple DNA probes, a study was conducted to evaluate the suitability of a tandemly reiterated sequence which encodes a T. vivax diagnostic antigen as a single probe for detection of this parasite. The antigen is recognized by monoclonal antibody Tv27 currently employed in antigen detection ELISA (Ag-ELISA). A genomic clone which contained a tetramer of the 832-bp cDNA sequence was isolated and shown to be more sensitive than the monomer. Oligonucleotide primers were designed based on the nucleotide sequence of the 832-bp cDNA insert and used in amplifying DNA sequences from the blood of cattle infected with T. vivax isolates from West Africa, Kenya, and South America. The polymerase chain reaction (PCR) product of approximately 400 bp was obtained by amplification of DNA from all the isolates studied. The oligonucleotide primers also amplified DNA sequences in T. vivax-infected tsetse flies. Subsequently, PCR was evalauted for its capacity to detect T. vivax DNA in the blood of three animals experimentally infected with the parasite. T. vivax DNA was detectable in the blood of infected animals as early as 5 days post-infection. Blood and serum samples from the three cattle and from six other infected animals were also examined for the presence of trypanosomes and T. vivax-specific diagnostic antigen. Trypanosomes appeared in the blood 7-12 days post-challenge, while the antigenemia was evident on Days 5-20 of infection. Analysis of the data obtained in the three animals during the course of infection revealed that the buffy coat technique, Ag-ELISA, and PCR revealed infection in 42, 55, and 75 percent of the blood samples, respectively. PCR amplification of genomic DNA of T. vivax is thus superior to the Ag-ELISA in the detection of T. vivax. More importantly, both the T. vivax diagnostic antigen and the gene encoding it are detectable in all the T. vivax isolates examined from diverse areas of Africa and South America.